(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
The Nullifying Legal Effect of the Implicit Act of Will under Canon 1101 §2 The article examines the concept of an implicit act of will under Canon 1101 § 2, which holds that a positive intent excluding an essential property of marriage - whether expressed explicity or implicity -renders consent null. After tracing the doctrine’s roots in pre‑1917 canon law and in two 19th‑century instructions of the Congregation of the Holy Office, it analyzes five jurisprudential models developed by the Roman Rota: (i) Actus in alio contentus, a direct reservation (e.g., “I may divorce if unfaithful”) that genuinely contains exclusion of indissolubility; (ii) Actus suis placitis accomodatus: inclusion in consent of a conflicting element (e.g., denial of procreation); (iii) Actus praesumptus: discredited presumption that one exclusion automatically implies another; (iv) Actus negativus: flawed theory equating omission of essential elements with positive exclusion; (v) Concludent behavior: inferring hidden intent from conduct and circumstances. The first two models are upheld as substantively valid and equivalent in effect to explicit exclusion, while the latter three are valuable only as evidentiary tools. The article concludes that implicit and explicit acts of will are both positive manifestations under Canon 1101 § 2, sharing the same invalidating force. SOMMARIO: 1- Introduzione - 2. Rilevanza sul piano sostanziale - 3. Configurazioni giurisprudenziali dell’atto implicito di volontà: a) Actus in alio contentus - b) Actus suis placitis accomodatus - c) Actus praesumptus - d) Actus negatives - e) Comportamento concludente - 4. Conclusioni.